Fertility and Female Labor Force Participation in Asian Countries; Panel ARDL Approach - Nazah, Nawalin; Duasa, Jarita; Arifin, Muhammad Irwan (Universitas Muhammadiyah Yogyakarta, 2021)
Fertility has a close relationship with female labor force participation and is predicted to be the prominent factor affecting female labor force participation in rich and emerging countries. The decline in fertility worldwide, accompanied by increased female education, is assumed to increase female labor force participation. The increase in the female labor force participation rate can improve economic incentives for the country. Therefore, this study estimates the effect of fertility and female education on female labor force participation in cross-country panel datasets from 39 Asian countries, using panel ARDL analysis from 1990-2018. This study also examines the panel causality between the variables employing Dumitrescu and Hurlin’s (2012) Granger non-causality test. According to the Hausman test, among the three models in panel ARDL, DFE is the preferred model compared to the PMG and MG. The results revealed that fertility was negatively significant on female labor participation in the short run but not in the long run. In contrast, female education was positively significant on female labor participation in the long run but not in the short run. Meanwhile, the panel causality showed a bidirectional relationship between female labor participation and fertility, female labor participation and education, and fertility and female education.